2001
DOI: 10.1128/aem.67.4.1775-1782.2001
|View full text |Cite
|
Sign up to set email alerts
|

Does the High Nucleic Acid Content of Individual Bacterial Cells Allow Us To Discriminate between Active Cells and Inactive Cells in Aquatic Systems?

Abstract: The nucleic acid contents of individual bacterial cells as determined with three different nucleic acid-specific fluorescent dyes (SYBR I, SYBR II, and SYTO 13) and flow cytometry were compared for different seawater samples. Similar fluorescence patterns were observed, and bacteria with high apparent nucleic acid contents (HNA) could be discriminated from bacteria with low nucleic acid contents (LNA). The best discrimination between HNA and LNA cells was found when cells were stained with SYBR II. Bacteria in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
300
2
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 354 publications
(325 citation statements)
references
References 29 publications
22
300
2
1
Order By: Relevance
“…It has previously been demonstrated that HDNA cells represent the active component of bacterioplankton communities, while LDNA cells are likely to consist of dormant or dead bacteria (Gasol et al, 1999;Lebaron et al, 2001Lebaron et al, , 2002.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been demonstrated that HDNA cells represent the active component of bacterioplankton communities, while LDNA cells are likely to consist of dormant or dead bacteria (Gasol et al, 1999;Lebaron et al, 2001Lebaron et al, , 2002.…”
Section: Resultsmentioning
confidence: 99%
“…Based on di¡erences in SYBR Green £uorescence (DNA content) and side scatter (an indicator of cell size), heterotrophic bacteria were divided into two distinct populations, high DNA (HDNA) and low DNA (LDNA) (Gasol et al, 1999;Lebaron et al, 2001Lebaron et al, , 2002 (Figure 1). It has previously been demonstrated that HDNA cells represent the active component of bacterioplankton communities, while LDNA cells are likely to consist of dormant or dead bacteria (Gasol et al, 1999;Lebaron et al, 2001Lebaron et al, , 2002.…”
Section: Resultsmentioning
confidence: 99%
“…Bouvier et al 2007 ) . The general pattern that emerges from the literature is that HNA cells appear to be not only larger cells but also more active cells, with high speci fi c metabolism and growth, and that changes in total bacterial abundance are often linked to changes in this fraction (Lebaron et al 2001 , but see Jochem et al 2004 ;Bouvier et al 2007 for other possible scenarios on this topic).…”
Section: Prokaryotic Cell Abundances Biomass and Productionmentioning
confidence: 99%
“…active as well as dormant, cells which possess an intact membrane (cf. Stevenson, 1978;Lebaron et al, 2001;Luna et al, 2002). IPL-GDGTs found in sediments and reported up to now as indicative of living Archaea are glycolipids with monohexose-and dihexose-GDGTs and GDGTs with a loss of m/z 341 (Biddle et al, 2006;Lipp and Hinrichs, 2009;Schubotz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%